2018
DOI: 10.2298/tsci180115215v
|View full text |Cite
|
Sign up to set email alerts
|

The importance of the capacity building for implementing energy efficiency and renewable energy solutions

Abstract: Original scientific paper https://doi.org/10.2298/TSCI180115215VWithin the Climate and Energy Directive, the European Commission has set three main targets: reduction of GHG emissions, increase a share of renewable resources, and improvements in energy efficiency. This paper introduces needs and solutions for capacity building in cross-border regions of Slovenia-Croatia-Hungary in order to better implement energy efficiency and renewable resources potentials. It was identified that a lack of knowledge by the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The negative relationship between education (capacity building) and energy security for Burkina Faso (the short‐run results) and Nigeria implies that capacity‐building efforts in the past have not focused on the need to produce and consume energy more sustainably. This finding is consistent with Virtič and Kovačič Lukman (2018) and Sendegeya and Chiguvare (2016). These studies highlight the essence of capacity building for energy efficiency, renewable energy and sustainable energy development.…”
Section: Discussionsupporting
confidence: 91%
“…The negative relationship between education (capacity building) and energy security for Burkina Faso (the short‐run results) and Nigeria implies that capacity‐building efforts in the past have not focused on the need to produce and consume energy more sustainably. This finding is consistent with Virtič and Kovačič Lukman (2018) and Sendegeya and Chiguvare (2016). These studies highlight the essence of capacity building for energy efficiency, renewable energy and sustainable energy development.…”
Section: Discussionsupporting
confidence: 91%
“…[119], the state of the art of Italian residential building heritage has been reviewed, while energy retrofit issues and viable solutions have been investigated by collecting literature examples and experiences, focusing on common retrofit measures on historical buildings per thematic area. Virtič and Kovačič Lukman [120] introduce needs and solutions for capacity building in cross-border regions of Slovenia-Croatia-Hungary in order to better implement energy efficiency and renewable resources potentials. It was identified that a lack of knowledge by the stakeholders represents a main obstacle for implementing more environmental and economic acceptable energy solutions on a local and regional levels.…”
Section: Energy Performance Improvements Of the Existing Buildingsmentioning
confidence: 99%
“…It is essential to provide stakeholders specific information from their points-of-view regarding the impact of energy strategies from their interest and to implement better renewable energy [14]. Though the project shows the community's acceptance, the responsibility to educate locals was somehow forgotten, as its result in the lack of maintenance throughout the works or the failure of decentralized renewables.…”
Section: • Capacity Buildingmentioning
confidence: 99%